International Law and the Legitimate Determination of Risk: Is Democratising Expertise the Answer? - Peel, Jacqueline (Victoria University of Wellington Law Review, 2007)
As technological risks become a matter of increasing concern around the world, standard science-based approaches for risk assessment are coming under increasing pressure to be responsive not only to expert views, but also broader public perspectives on risks and concerns over possible uncertainties. International fora in which national risk regulations are reviewed for their scientific adequacy, such as WTO dispute processes under the SPS Agreement, have become the focus for debates over whether such processes allow adequate scope for “democratic” risk concerns as well as scientific views. This article assesses the scope for democratising expertise in international risk determination, using reforms suggested in the context of WTO SPS disputes as a case study. It contends that the institutional ramifications for international law of “democratising expertise” are far from clear, especially given the obstacles encountered in establishing democratic procedures for transparency and participation at the global level. This is not a reason to abandon efforts for greater democratisation of supranational risk determination but points to the need for more nuanced approaches for balancing scientific and political concerns in risk decision-making in order to ensure outcomes which are broadly acceptable.